Identification and Characterization of Different Types of Plastics Wastes Using X-Ray Diffraction and X-Ray Fluorescence Techniques - Abubaker, Shawbo A.; chaqmaqchee, Faten A.; Taha, Akram H. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2021)
In this study, different types of polymers in postconsumer plastics with pure plastics have been studied. Highdensity polyethylene (HDPE1 and HDPE2), polyvinyl chloride (PVC3 and PVC4), polyethylene terephthalate (PET5 and PET6), and polypropylenes (PP7 and PP8) were compared using X-ray diffraction (XRD) and X-ray fluorescence (XRF) techniques. XRF has shown the spectral in K-lines of polymer materials present in plastics waste. The peak intensity and degree of crystallinity of commercial polymers are varied using XRD analysis. The intensity not attributable to the crystalline peaks may be regarded as the amorphous scattering and used as a template in analyzing the diffraction pattern of the samples. The XRD analysis helps to provide characteristic spectral lines whose intensities vary with the type of each constituent polymer. The combined usage of XRD and XRF techniques yielded very useful and effective results for a commercial plastic management.